The recruiter : spying and the lost art of American intelligence - London, Douglas (Operations officer) (Hachette Books, 2021)
"A revealing CIA memoir from a 34-year veteran of the agency who worked as a case officer and recruiter of foreign agents before and after 9/11 -- full of rich details and sharp assessments -- providing an invaluable perspective on the state of modern spycraft, how the CIA has developed, and how it must continue to evolve"--